2022
DOI: 10.3389/fonc.2022.920916
|View full text |Cite
|
Sign up to set email alerts
|

Survival outcomes analysis according to mismatch repair status in locally advanced rectal cancer patients treated with neoadjuvant chemoradiotherapy

Abstract: BackgroundThe predictive role of mismatch repair (MMR) status for survival outcomes and sensitivity in neoadjuvant chemoradiotherapy settings for patients with locally advanced rectal cancer (LARC) has been inconclusive.MethodsA retrospective cohort of patients with LARC treated with neoadjuvant chemoradiotherapy (nCRT) was recruited. After adjusting for baseline characteristics, we used propensity score matching to reduce the effect of potential confounding factors on MMR status. The primary analysis was base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“… 24 Conversely, Chen et al found there were better overall survival rates for LARC patients with dMMR status after nCRT. 25 Kim JH et al also demonstrated the prognostic features of MSI-H CRCs include a favorable survival of patients. 26 There may be two main reasons for this: One possible explanation for the converse result involves different nCRT regimens, such as consolidation chemotherapy with Capeox or mFOLFOX6 regimens can significantly improve survival, 27 , 28 while a limited effects of fluoropyrimidines may happened during nCRT.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“… 24 Conversely, Chen et al found there were better overall survival rates for LARC patients with dMMR status after nCRT. 25 Kim JH et al also demonstrated the prognostic features of MSI-H CRCs include a favorable survival of patients. 26 There may be two main reasons for this: One possible explanation for the converse result involves different nCRT regimens, such as consolidation chemotherapy with Capeox or mFOLFOX6 regimens can significantly improve survival, 27 , 28 while a limited effects of fluoropyrimidines may happened during nCRT.…”
Section: Discussionmentioning
confidence: 97%
“…All patients underwent chemoradiotherapy before total mesorectal excision, which defined as neoadjuvant chemoradiotherapy, including chemotherapy regimens with fluorouracil/oxaliplatin, and radiotherapy was administered at 2.0 Gy in 25 fractions over 5 weeks, with a total dose of 50 Gy (24)(25)(26). Physical examinations and computed tomography scans were performed every 3-6 months for the first 1 year and every 6 months for the following 2 years after TME as a routine follow-up strategy for all patients.…”
Section: Treatment and Follow-upmentioning
confidence: 99%
“…The MYC oncogene is part of the gene superfamily, and its product is commonly activated in human cancers (94,95). The mechanisms by which MYC activation promotes tumor progression mainly involve cell proliferation, cell invasion, metabolic reprogramming, genomic instability, angiogenesis, and immune evasion (96,97). MYC can reshape the tumor microenvironment, evading host immune responses (98).…”
Section: Discussionmentioning
confidence: 99%
“…Following H. pylori infection, phagocytes that have gathered in the stomach mucosa produce O2•, HO•, and HOCl (95). Rat gastric mucosal cells have been shown to undergo apoptosis when exposed to NH 2 Cl (96).…”
Section: Gastric Adenocarcinoma and Gastric Cancermentioning
confidence: 99%
See 1 more Smart Citation